Contemporary Russian philosophical studies and evaluations of Sergei Bulgakov’s philosophy - Wang, Shuo (Studies in East European thought, 2025)
Given the cultural significance of the Silver Age religious renaissance in the history of Russian thought, it is important to examine how contemporary Russian philosophers, amidst increasing academic specialization, approach and categorize indigenous religious philosophy from this period. This article investigates contemporary Russian philosophical research and its evaluations of Sergei Nikolayevich Bulgakov, a key Silver Age figure. This study finds that, following the surge in research during the 1990s, Russian scholars have maintained consistent interest in Bulgakov. However, within the discipline of philosophy these researchers may still be facing some structural problems. Bulgakov’s philosophical and theological ideas are intrinsically linked, which makes it difficult to pinpoint his disciplinary orientation. Researchers have been obliged to adjust their approaches to overcome misunderstandings. Not only philosophy of language but also philosophy of science and technology have been influenced by this new interest in Bulgakov. The overall trend in the examination of Bulgakov’s intellectual legacy has been toward careful and balanced deliberation and analysis.